Identificação e caracterização de componentes da via de excisão de bases (BER) em cana-de-açúcar (SACCHARUM spp.) - Medeiros, Nathalia Maíra Cabral de (2018)
The productivity of any cultivar is directly related to the preservation of its genetic code, since any change in the sequence can have consequences that directly affect the development/growth of the plant. The response to DNA damage occurs through its repair through different pathways, one of which is the base excision pathway (BER), whose studies on plants are still inferior in comparison to other eukaryotic organisms. One of the obstacles in the advancement of these researches is the complexity of the plant genome present in some cultivars of agroeconomic importance, so that many studies use diploid models organisms. This work proposes to fill the gap in the knowledge of the BER pathway in relation to non-models and polyploid plants, targeting the sugarcane. The first approach of the work was to identify components of the BER pathway in sugarcane and compare the results obtained with the sequences of other plant organisms to deepen the question of conservation of this pathway. The second approach was using a sequence homologous to the AP endonuclease of Arabidosis thaliana (AtARP) in sugarcane denominated ScARP1. This was the subject of an enzymatic characterization test. For the first approach, we considered the results of previous studies, where a duplication in sugarcane was verified for the AP endonuclease sequence (ScARP1 and ScARP3), in addition to recent work on the BER pathway review in plants. Thus, a search of the ESTs sequences databases for sugarcane (SUCEST-FUN) was done by sequences belonging to via BER. To verify the occurrence of duplications, the results of this search were submitted to phylogenetic analysis and Bayesian inferences. The sequences found were characterized as the presence of conserved domains, besides some of them were modeled, creating hypothetical 3D models. Some of the presumed proteins identified differed in their structure with the reference proteins of A. thalina. Furthermore, multiple copies sequences were observed in certain plant families over others. For the second approach, the ScARP1 protein was cloned, expressed and purified. With this, different assays were carried out to evaluate its enzymatic efficiency (considering temperature, enzymatic cofactors and salt concentration), as well as the substrates that would be recognized by ScARP1. It has been observed that the ScARP1 protein has only AP endonuclease activity. In addition, partial complementation of ScARP1 in protein extracts of the A. thalina arp-/- mutant was observed. With this work it was possible to identify members of the BER pathway in sugarcane, besides characterizing them structurally and phylogenetically, which made it possible to highlight differences between sequences of monocotyledons and dicotyledons. Furthermore, in relation to ScARP1, it was determined that this presents Ap endonuclease activity essential for his performance in BER. Thus, it amplified the knowledge this pathway in sugarcane and vegetables on organisms in general.